Determining the importance of competency and person-job fit for the job performance of service SMEs employees in Malaysia - June, Sethela; Yeoh, Khar Kheng; Mahmood, Rosli (Canadian Center of Science and Education, 2013)
The small and medium enterprises (SMEs) have contributed to the economic growth and competitiveness of many countries. However, as the SMEs continue to grow as an important entity in many economies including Malaysia, many factors have dampened such progress.While previous studies had focused on its macro perspective in terms of firm level and industry level performance, this study attempted to address the basic issue of SMEs employees in terms of their job performance.This study is underpinned by the theory of job performance and further supported by the theory of congruence.The main objective of this research is to investigate on the relationship that may exist between three variables comprised of competency, person-job fit and the employees’ job performance in the context of service SMEs.Using a quantitative method, a sample of 324 responses was collected using a mail survey from 1500 distributed questionnaires.Results show significant relationships between competency, person-job fit and the job performance of employees.Conclusions and implications of the study were discussed.